Successful liver transplantation in critically ill patient (Case report) - M. Sh. Khubutia; S. V. Zhuravel; N. K. Kuznetsova; I. V. Alexandrova (Трансплантология (Москва), 2016)
This article is an example of a successful liver transplant patient in critical condition.